1997
DOI: 10.3171/jns.1997.87.2.0190
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral cavernous malformations: natural history and prognosis after clinical deterioration with or without hemorrhage

Abstract: Despite recent studies of the natural history of cavernous malformations, there remains significant uncertainty concerning hemorrhage rates and the importance of lesion location. Controversy arises over varying definitions of "hemorrhage." What is ultimately important to the patient is the occurrence of a neurological event, which may or may not be associated with radiologically documented hemorrhage, as well as the chance of recovery after such an event. The purpose of this study was to determine the rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
370
4
17

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(403 citation statements)
references
References 18 publications
12
370
4
17
Order By: Relevance
“…Robinson et al 26 reported an annual hemorrhage rate of 0.7% per lesion-year. The studies of Kondziolka et al, 15 Moriarity et al, 20 and Porter et al 23 reported annual hemorrhage rates ranging from 1.6% to 3.1% per patient-year. Across these 3 studies including a total of 363 patients followed up for 1121.5 patient-years, the overall hemorrhage rate was 2.4% per patient-year.…”
Section: Hemorrhagementioning
confidence: 99%
See 2 more Smart Citations
“…Robinson et al 26 reported an annual hemorrhage rate of 0.7% per lesion-year. The studies of Kondziolka et al, 15 Moriarity et al, 20 and Porter et al 23 reported annual hemorrhage rates ranging from 1.6% to 3.1% per patient-year. Across these 3 studies including a total of 363 patients followed up for 1121.5 patient-years, the overall hemorrhage rate was 2.4% per patient-year.…”
Section: Hemorrhagementioning
confidence: 99%
“…7,8,14,15,20,23,26 Developmental venous anomalies were seen in 54 (9%) of 593 patients in 6 studies reporting associated vascular malformations. 7,15,20,23,26,31 Table 2 summarizes overall epidemiological, clinical presentation, and hemorrhage rate data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suas paredes são constituídas de células endoteliais simples e fina camada fibrosa de adventícia. Não possuem camada muscular, lâmina elástica e não existe tecido nervoso no seu interior 1,3,5 . Eles podem apresentar tromboses, calcificações e frequentemente são encontrados produtos de degradação sanguí-nea em vários estágios de evolução, sugerindo a ocorrência de repetidos sangramentos no interior da lesão 8,10 .…”
Section: Discussionunclassified
“…5,7,[13][14][15][16]21) Neurological deficits are likely to worsen due to repeated hemorrhages, so the current trend is toward aggressive management of lesions reaching the pial or ependymal surface of the brainstem, but extreme care is required perioperatively since vital structures in life-support functions are located at the brainstem. 2,5,9,[11][12][13][14]16,21) Direct resection through various approaches has been used for cavernous malformations located primarily in the midbrain and pons since there is only minor risk of inflicting further neurological damage. 4,6,8,[10][11][12][17][18][19] The indications for surgical treatment and selection of the most appropriate surgical routes may be indeterminable for cavernous malformations with neither bulging nor extension into the pial or ependymal surface.…”
Section: Introductionmentioning
confidence: 99%